2018
DOI: 10.18203/2349-3291.ijcp20182581
|View full text |Cite
|
Sign up to set email alerts
|

Resilience level among adolescent children: a school-based study in Kolkata, India

Abstract: INTRODUCTIONOnce upon a time, the school days were called the best part of one's life. If we rewind back by only 2 decades, we would find children are going school with much lighter weights on their back as well as on their brain. The rat race of modern life is affecting each and every strata of our society and students are not exempted from this decadence.The unmet virtual needs of life, the gap between demand and achievement are affecting our health, to be precise, our mental health silently and the worst su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…The Adolescent Resilience Scale from Japan by Oshio et al (2003) although mentioned adolescents in the title of the scale actually developed for and standardized on older teens and adults (aged 19–23 years), therefore also excluded from the present analysis. There are few scales that are tested with Indian sample but either with a very small (e.g., CYRM by Unger & Leibenberg with 2 samples for qualitative and 60 samples for India for quantitative analysis of the scale testing) and nonrepresentative sample size (e.g., Wagnild and Young’s RS, 1993 was used in 130 school going adolescents aged 14–18 years in two different studies reported by Azam in 2012 and Azam & Shaikh in 2011) or without reporting the psychometric properties (e.g., Conner Davidson Resilience Scale for Children, 2003, for Kannada speaking adolescents; CYRM used in 157 school going adolescents in Kolkata by Banerjee et al, 2018). Resilience Scale for Adolescents was used with one hundred fourteen 15- to 16-year-old adolescents by Annalakshmi (2009b), however not validated with Indian samples.…”
Section: Discussionmentioning
confidence: 99%
“…The Adolescent Resilience Scale from Japan by Oshio et al (2003) although mentioned adolescents in the title of the scale actually developed for and standardized on older teens and adults (aged 19–23 years), therefore also excluded from the present analysis. There are few scales that are tested with Indian sample but either with a very small (e.g., CYRM by Unger & Leibenberg with 2 samples for qualitative and 60 samples for India for quantitative analysis of the scale testing) and nonrepresentative sample size (e.g., Wagnild and Young’s RS, 1993 was used in 130 school going adolescents aged 14–18 years in two different studies reported by Azam in 2012 and Azam & Shaikh in 2011) or without reporting the psychometric properties (e.g., Conner Davidson Resilience Scale for Children, 2003, for Kannada speaking adolescents; CYRM used in 157 school going adolescents in Kolkata by Banerjee et al, 2018). Resilience Scale for Adolescents was used with one hundred fourteen 15- to 16-year-old adolescents by Annalakshmi (2009b), however not validated with Indian samples.…”
Section: Discussionmentioning
confidence: 99%
“…9 Despite not being validated, some studies using the CYRM-28 are reported in the Indian literature on resilience. 18,19 However, these studies neither confirmed its factor structure in the Indian context nor documented its psychometric properties. As highlighted previously, different factor structures emerged from the validation studies of the CYRM-28 in different cultural contexts; hence, it becomes imperative to establish its construct validity and examine its psychometric properties in India, both in English and in Hindi, as Hindi is the most widely spoken and understood language in our country (43.63%).…”
Section: Introductionmentioning
confidence: 93%
“…Spor ve egzersiz gibi fiziksel aktiviteler, bireylerin sosyal yeterliliğinin ve özerkliğinin gelişmesine, fiziksel açıdan sağlıklı olmasına ve kendini güçlü hissetmesine aracılık ederek psikolojik sağlamlığın gelişimine katkı sunmaktadır (Banerjee et al, 2018;Mohammadinia et al, 2018, Young et al, 2019. Egzersiz yapma ile psikolojik sağlamlık arasında pozitif yönlü ilişkilerin olması ve COVİD 19 sürecinde egzersiz yapanların egzersiz yapmayanlara göre psikolojik dayanıklılıklarının daha yüksek olduğunun ortaya konulmuş olması (Çifçi ve Demir, 2020) sporun zorluklarla mücadeledeki önemini ortaya koymaktadır.…”
Section: şEkil 2 Araştırma Modeliunclassified